Annals 2 - Poulsen, Aske Damtoft (The Oxford Critical Guide to Tacitus, 2025)
This chapter offers three complementary perspectives on Annals 2. Section one identifies deceit and deception as the major theme and analyzes how this theme is developed in and connects the various narratives of the book. Section two investigates an example of Tacitus’ historiographical mode that comes to the fore in Annals 2, namely the loosening of the annalistic structure for rhetorical effect, with particular emphasis on how it is used to reinforce the focus on deceit and deception. Finally, section three explores the reader’s experience: How does it feel to read Annals 2? Through analysis of his treatment of the hopes attached to Germanicus (spes Germanici), it demonstrates how Tacitus exploits the tension between ignorant characters and omniscient readers in historiography to devastating emotional effect.